2014
DOI: 10.1021/jp504537n
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties of Dense Hard Sphere Packings

Abstract: The structural properties of dense random packings of identical hard spheres (HS) are investigated. The bond order parameter method is used to obtain detailed information on the local structural properties of the system for different packing fractions φ, in the range between φ = 0.53 and φ = 0.72. A new order parameter, based on the cumulative properties of spheres distribution over the rotational invariant w6, is proposed to characterize crystallization of randomly packed HS systems. It is shown that an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 70 publications
2
33
0
Order By: Relevance
“…It is important to note that the distinction between face-adjacent and edge-connected tetrahedra is instrumental in detecting the presence of either hexagonal closely packed or FCC crystalline patterns (hexagonal closely packed and FCC patterns are, respectively, built upon face-adjacent or edge-connected tetrahedra). To date, the selection of one pattern or the other remains an outstanding question for crystal formation in athermal systems853. Recent studies on macroscopic packings have revealed that both crystalline motifs coexist in highly crystalline packings with a slight preference for the FCC pattern313.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the distinction between face-adjacent and edge-connected tetrahedra is instrumental in detecting the presence of either hexagonal closely packed or FCC crystalline patterns (hexagonal closely packed and FCC patterns are, respectively, built upon face-adjacent or edge-connected tetrahedra). To date, the selection of one pattern or the other remains an outstanding question for crystal formation in athermal systems853. Recent studies on macroscopic packings have revealed that both crystalline motifs coexist in highly crystalline packings with a slight preference for the FCC pattern313.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the significance of regular packings in a wide range of fields, from fundamental physics to granular processing67, the basic mechanism of crystallization in this highly dissipative material is still unknown. Indeed the transition from disordered to ordered packings triggers a wide range of geometrical, topological and mechanical changes at multiple length scales, some of which have just recently been uncovered48910111213. To describe this complexity and since sphere packings are comprised of numerous particles, it is tempting to use a statistical approach.…”
mentioning
confidence: 99%
“…Figure 3 shows typical temporal variations of parameters q 4 , q 6 , and w 6 for solid-like and liquid-like LJ systems in the vicinity of the melting transition; strong fluctuations of the parameters make it clear to use the probability distribution functions (PDF) taken over q l and w l values −P (q l ) and P (w l ) to characterize the solid-liquid transition of different close-packed solids (Klumov 2010(Klumov , 2013Klumov et al 2011;Mitic et al 2013). By varying the number of nearest neighbors N nn and rank l of bondorder parameter, it is possible to identify any lattice type (including quasicrystalline particles and distorted hcp/fcc/ico modifications) existing in the system (e.g.…”
Section: Orientational Local Order At Meltingmentioning
confidence: 99%
“…Here, we also consider the properties of orientational order of LJ particles near the melting transition (Steinhardt et al 1983;Nose and Yonezawa 1986;Mitic et al 2008;Klumov 2010Klumov , 2013Klumov et al 2011) to quantify the solid-liquid transition (e.g. Microscopic nature of melting is not fully understood yet even for simple systems, like Lennard−Jones (LJ) one, although it is well understood in numerous experimental and theoretical investigations that the physical and mechanical properties of condensed matter are determined primarily by the short-range order of atoms.…”
Section: Introductionmentioning
confidence: 99%
“…The search for crystal-like clusters is a common method in the study of crystal nucleation and growth [6,24,25]. Actually, the frequency of specific ordered structures, such as the dimer in tetrahedra [26] and the face centered cubic (or hexagonal close-packed) structure in spheres [27], is strongly correlated to local order degree. In disk packings, both the melting and jamming transitions with the emergence of local hexatic order had been demonstrated by a number of researches [15,28,29].…”
Section: Introductionmentioning
confidence: 99%